Maximizing the Potential of Digital Learning Media in Primary Education: Insights from a Systematic Literature Review - Salam, Nisrina; Suyanto, Slamet; Ningsih, Sri Nurfadillah (Universitas Pendidikan Ganesha, 2024)
The rapid advancement of technology in the era of the Industrial Revolution 4.0 has significantly encouraged the widespread adoption of technology-based learning. Digital learning media have become a crucial element in education; however, their utilization remains suboptimal due to teachers' limited understanding and skills in using these technologies. Thus, a comprehensive study is needed to analyze the effectiveness of digital media in learning processes. This study aims to evaluate the effectiveness of various types of digital learning media in primary education. The research employs a Systematic Literature Review (SLR) approach, reviewing 34 journals published between 2020 and 2023. Articles were identified using databases with the help of the Publish or Perish software and PRISMA methodology. The findings reveal that the most commonly used digital media are videos, Android-based applications, and interactive multimedia. These media are predominantly applied in science, mathematics, and social studies subjects and are more frequently utilized in upper-grade classrooms. Furthermore, the results indicate that the application of digital media in learning has proven effective in enhancing students' academic performance, affective domains, language skills, critical thinking skills, and knowledge. This study provides valuable insights for maximizing the potential of digital media to support learning at the primary education level.